Deconfinement and chiral restoration in non-local PNJL models at zero and imaginary chemical potential - Pagura, Valeria Paula (2012)
We study the deconfinement and chiral restoration transitions in the context of non-local PNJL models, considering the impact of the presence of dynamical quarks on the scale parameter appearing in the Polyakov potential. We show that the corresponding critical temperatures are naturally entangled for both zero and imaginary chemical potential, in good agreement with lattice QCD results. We also analyze the Roberge-Weiss transition, which is found to be first order at the associated endpoint.